2018
DOI: 10.5055/jom.2008.0005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fentanyl dosage and immune function in the postoperative period

Abstract: Background: Anesthesia and surgery are associated with impairment of the immune system expressed as an excessive proinflammatory immune response and suppression of cell mediated immunity. Opioids, an integral part of anesthetic technique, possess an inhibitory effect on both humoral and cellular immune responses. It was the aim of the present study to examine the effect of various doses of fentanyl on cytokine production during the perioperative period.Intervention: The effect of large (LDFA, 70-100 μg/kg), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 0 publications
1
28
0
2
Order By: Relevance
“…8 This study found that both doses had the same effect on NKCC on the first postoperative day; however, patients exposed to the low dosage showed faster recovery of NKCC suppression, while patients given the higher doses of fentanyl still showed suppression 48 hours after surgery. 8 Similar findings were reported in a study by Yardeni et al 27 who investigated the ex vivo effects of high, intermediate, and low doses of fentanyl on immune function during the postoperative period of 60 patients. Secretion of the proinflammatory cytokines IL-1 and IL-6 were significantly diminished in patients treated with the high and intermediate doses of fentanyl when compared with the low dose.…”
Section: Fentanylsupporting
confidence: 82%
See 1 more Smart Citation
“…8 This study found that both doses had the same effect on NKCC on the first postoperative day; however, patients exposed to the low dosage showed faster recovery of NKCC suppression, while patients given the higher doses of fentanyl still showed suppression 48 hours after surgery. 8 Similar findings were reported in a study by Yardeni et al 27 who investigated the ex vivo effects of high, intermediate, and low doses of fentanyl on immune function during the postoperative period of 60 patients. Secretion of the proinflammatory cytokines IL-1 and IL-6 were significantly diminished in patients treated with the high and intermediate doses of fentanyl when compared with the low dose.…”
Section: Fentanylsupporting
confidence: 82%
“…However, similar suppression of NKCC and IL-2 secretion was observed among the three groups . 27 Yeager et al 28 administered fentanyl to seven healthy volunteers at an initial dose of 3 µg/kg followed by an infusion of 1.2 µg/kg/h for 2 hours to evaluate the effects on innate and acquired immunity in humans and on leukocyte subpopulations in peripheral blood. This short-term exposure to fentanyl produced a significant increase in circulating CD16+ and CD8+ lymphocytes.…”
Section: Fentanylmentioning
confidence: 99%
“…Non-sterile intravenous drug use, including needle sharing, is one possible mechanism for this effect; however, opiates also produce abnormalities in defensive immune parameters. Consistent with the latter, heroin users exhibit decreases in circulating lymphocytes, natural killer (NK) cell activity, cytokine production, and antibody-dependent cellular cytotoxicity (Govitrapong et al, 1998; Nair et al, 1986; Yardeni et al, 2008). Similarly, rats treated with morphine, the centrally active metabolite of heroin, exhibit lower rates of lymphocyte proliferation, splenic NK cell activity, blood lymphocyte proliferation, and proinflammatory cytokine production (Fecho et al, 1993a; Fecho et al, 1993b, 1996a,b; Lysle et al, 1993; Saurer et al, 2006a,b).…”
Section: Introductionmentioning
confidence: 93%
“…This study showed that both doses induced an inhibition of NK cytotoxicity on the first postoperative day; however, patients on the low dosage recovered faster, while patients on higher doses still showed reduction of immune parameters 48 h after surgery. These results were confirmed by Yardeni et al (24), who studied the effect of high (70- In a randomized controlled trial of 25 patients undergoing neck surgery, NK activity was assessed in patients treated with either fentanyl of flurbiprofen. In fentanyl treated patients NK cell cytotoxicity was suppressed more than in patients treated with flurbiprofen on day 1, but not day 2 postoperatively (25).…”
Section: Human Studiesmentioning
confidence: 62%
“…The immunosuppressive properties of fentanyl have been consistently observed also in the human. The drug affects cellular immune responses and cytokine production in patients and healthy volunteers in a dose related fashion (1,2,(21)(22)(23)(24).…”
Section: Human Studiesmentioning
confidence: 99%